Bangladesh Orthodontic Society represented 8th Asia Pacific Orthodontic Society (APOS) conference, New Delhi, 29th Nov-2nd Dec 2012 - Hossain, MZ (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2018)
Abstract not available Ban J Orthod & Dentofac Orthop, April 2014; Vol-4 (1-2), P.36-37